2011
DOI: 10.1021/ja108228x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hepatitis B Virus Capsids by Resistive-Pulse Sensing

Abstract: We report characterization of Hepatitis B virus (HBV) capsids by resistive-pulse sensing through single track-etched conical nanopores formed in poly(ethylene terephthalate) membranes. The pores were ~40 nm in diameter at the tip, and the pore surface was covalently modified with triethylene glycol to reduce surface charge density, minimize adsorption of the virus capsids, and suppress electroosmotic flow in the pore. The HBV capsids were assembled in vitro from Cp149, the assembly domain of HBV capsid protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
134
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 33 publications
1
134
0
Order By: Relevance
“…3 The resistive-pulse technique has been widely applied to size single molecules, viruses, particles and cells. [1][2][3][4][5][6][7][8][9][10][11][12] A single object passing through a pore causes a transient change of the system resistance, which is detected as a transient change of the transmembrane current, called a resistive-pulse. 6,7 The pulse amplitude is a measure of the object size while the pulse duration can be correlated with its surface charge.…”
Section: Introductionmentioning
confidence: 99%
“…3 The resistive-pulse technique has been widely applied to size single molecules, viruses, particles and cells. [1][2][3][4][5][6][7][8][9][10][11][12] A single object passing through a pore causes a transient change of the system resistance, which is detected as a transient change of the transmembrane current, called a resistive-pulse. 6,7 The pulse amplitude is a measure of the object size while the pulse duration can be correlated with its surface charge.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of applying nanopores to the analysis of nucleic acids, in particular DNA sequencing, has generated interest 3 , and motivated fundamental studies of the physics of nanopore translocations [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . The uses of solid-state nanopores have recently expanded to include detecting single proteins 18 , mapping structural features along RecA-bound DNA-protein complexes 19 and detecting spherical and icosahedral virus strains [20][21][22] . Such advances underline the importance of expanding our understanding of nanopore translocations beyond the case of DNA.…”
mentioning
confidence: 99%
“…Nowadays nanofluidic has become a fundamental and critical technique to study nano-scale fluidic, molecular and ion properties due to the special phenomena only occur in nanochannels (Sparreboom et al 2009;Freedman et al 2013). In recent 5 years, a substantial amount of research has been reported such as protein analysis (Chun et al 2013;Sang et al 2013), DNA stretching (van Kan et al 2012;Pedersen et al 2013), virus characterization (Zhou et al 2011) and ion separation (Tsukahara 2010;Gillespie and Pennathur 2013) based on nanofluidic chips.…”
Section: Introductionmentioning
confidence: 99%